Research Progress on Material Creep Experiments - Li, Jinhang; Zhang, Yanshen; Weng, Jiexin; Zhang, Xuan (International Journal of Materials Science and Technology Studies, 2025)
Creep behavior in solid propellants, characterized by time-dependent deformation under constant load, critically impacts the structural integrity and operational safety of rocket motors. This paper reviews recent advancements in creep research across three dimensions: (1) Macro-meso characterization techniques, including innovative indentation methods and high-resolution micro-CT/SEM imaging, which elucidate damage evolution mechanisms such as pore nucleation and crack propagation; (2) Multi-factor influences, revealing temperature-stress synergies, filler-matrix interactions, aging effects, and loading-rate dependencies that govern creep dynamics; (3) Cross-material experimental progress, highlighting breakthroughs in cementitious materials (20% prediction accuracy improvement), soft matter rheology (80% testing acceleration), and polymer microstructure transitions. While current studies have established comprehensive creep databases and advanced constitutive modeling, challenges remain in understanding long-term damage accumulation and multi-physics coupling under extreme conditions. Future directions emphasize in-situ multi-scale monitoring, cross-scale computational frameworks, and AI-driven predictive models for next-generation creep-resistant materials.